Cytotoxic Lesions of the Corpus Callosum: A Case Series - Leyla Mirzayeva; Nil Tokgöz; Emetullah Cindil (Current Research in MRI, 2024)
Various clinical conditions such as encephalitis, spontaneous intracranial hypotension, childbirth, trauma, use of antipsychotic and chemotherapeutic drugs, and subarachnoid hemorrhage may cause high-signal lesions in the splenium of the corpus callosum on diffusion-weighted imaging, which are referred to as cytotoxic lesions of the corpus callosum. In this article, we aimed to present the cytotoxic lesions of the corpus callosum, which were detected incidentally in patients who underwent brain magnetic resonance imaging for different reasons in our center.